Effects of the PRIMROSE prevention trial of childhood obesity on parental self-efficacy - Nora Döring; Ata Ghaderi; Johanna Enö Persson; Per Tynelius; Finn Rasmussen; Benjamin Bohman (BMC, 2021)
Abstract Background Parental self-efficacy (PSE) has been suggested as a key factor for enabling parents to support children in the development of healthy dietary and physical activity behaviors and to prevent childhood obesity. However, studies of intervention effects on PSE are lacking. The present study involved a secondary analysis of data on PSE collected in a previous primary prevention trial of childhood obesity called the PRIMROSE trial. The trial involved a family-based intervention using motivational interviewing and principles of cognitive-behavioral therapy within a social-cognitive theory framework. Methods In the PRIMROSE trial, parents and their children were randomly allocated to the intervention or usual care. In the present study, 928 mothers who responded to the Parental Self-Efficacy for Promoting Healthy Physical Activity and Dietary Behaviors in Children Scale (PSEPAD) at follow-up assessment were included. Data were analyzed using linear regression based on generalized estimating equations, with adjustment made for PSE at baseline. Results At follow-up assessment, there was a statistically significant difference of 1.4 units, 95% CI [0.4, 2.4], p = 0.009, between the intervention and control conditions on the subscale of the PSEPAD concerning PSE for promoting healthy dietary behaviors in children. However, this difference was deemed as without clinical importance. On the total scale or other subscales of the PSEPAD there were no statistically significant differences in PSE between conditions. Conclusions There was a statistically significant, but not clinically meaningful, intervention effect on PSE. However, because previous research repeatedly has shown positive associations of PSE with dietary and physical activity behaviors in children and that self-efficacy mediates behaviors, the construct may be important for influencing dietary and physical behaviors in children. Therefore, more research is warranted evaluating the effects of interventions on PSE in the context of childhood obesity prevention. Trial registration Retrospectively registered 9 October 2013 at ISRCTN (ISRCTN16991919 ).